2021
DOI: 10.4236/ce.2021.128133
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Role of “Religious People” in Environmental Conservation from the Perspective of Islamic Studies Students

Abstract: Protecting and conserving the environment is the responsibility of every individual including religious people in the Islamic context. Religious people play an important role in environmental conservation because they have the ability to cultivate public awareness on environmental conservation by linking the field of environmental conservation with religious knowledge. However, studies that focus on the role of religious people in helping the efforts of environmental conservation are still lacking. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…H5 is not accepted, indicating that the halal-green awareness of Muslim Generation Z consumers is not influenced by religiosity. The findings of this study contradict the research findings of Nurhayati and Hendar (2020) and Rahman and Jalil (2021) that there is a relationship between religiosity and halal and consumer green awareness. However, the study by Handriana et al (2021) found that religiosity does not significantly affect consumer awareness of natural halal cosmetic products.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…H5 is not accepted, indicating that the halal-green awareness of Muslim Generation Z consumers is not influenced by religiosity. The findings of this study contradict the research findings of Nurhayati and Hendar (2020) and Rahman and Jalil (2021) that there is a relationship between religiosity and halal and consumer green awareness. However, the study by Handriana et al (2021) found that religiosity does not significantly affect consumer awareness of natural halal cosmetic products.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Handriana (2021) found no that religiosity had no effect on awareness of natural halal cosmetic products. In addition, research conducted by Rahman and Jalil (2021) showed a relationship between religiosity and environmental awareness. Practicing Muslims have the ability to integrate knowledge based on the Quran and Hadith in providing awareness about environmental conservation efforts.…”
Section: Religiosity and Halal-green Awarenessmentioning
confidence: 99%
“…Third, "if everyone works together, we can address environmental issues (since religion calls for people to assist one another in goodness)". Religion teaches that in order to address environmental issues, we must cooperate or work together (Rahman & Jalil, 2021). This collaboration can be done in the context of multi-faith dialogical initiatives and program (Sayem, 2020).…”
Section: Domain and Questionnaire Itemmentioning
confidence: 99%
“…[6] Islamic studies students in Malaysia recognize the importance of the role of religious people in environmental conservation, and their proposed roles are in line with Islamic values related to environmental conservation. [1], The influence of social and religious factors on environmentally ethical behaviour (EEB) of the Muslim community in Malaysia has also been studied, and young Muslim environmental activists base their environmentalism firmly on their Muslim faith. [7] The Malay rural traditional village landscape is under pressure to being transformed into other uses to fulfil current socio-economic needs and rapid urbanization, but some development continues to erode the natural environment and cultural values that embody the landscape that has maintained the traditions are under threat.…”
Section: Belief Systemsmentioning
confidence: 99%